Assessment of economic impact through transfer of weather forecast and Agro-advisory for Farmers in South Alluvial Indo-Gangetic plain of Bihar - KUMAR, SUNIL (Journal of Soil and Water Conservation, 2025)
The economic impact assessment is the key to know the benefit from any technology for farmers. Present study was conducted during Summer and Kharif in 2022 and 2023 at villages of districts which comes under the South Alluvial Indo-Gangetic Plain of Bihar to know the effectiveness and usefulness of Agro Advisory Services (AAS) and to quantify the economic benefits through adopting the agromet advisory in their regular agricultural operations. For this purpose, two groups of farmers were selected namely, a group adopting the agromet advisories regularly in their operation (AAS farmers) and other group of farmers not aware of agromet advisories (Non-AAS farmers). The crop growth and yield was observed to be good and high in case of farmers who have adopted the AAS information regularly compared to the farmers who have not adopted the AAS information. In kharif rice, maize and brinjal monetary value of saving was estimated as Rs. 1190, Rs. 1600 and Rs. 2,60,000 per hectare. Similarly, in case of summer season Moong, Okra, Mango and Litchi are cultivated and the benefit to the Growers was estimated as Rs. 2100/-, 3,20,000/-, 4,00,000/- and 8,40,000/- per hectare to adoptive farmers of the locality. The estimated loss to the non-adoptive farmers who did not care the Advice rendered by Agromet advisories Served by this centre was estimated at 140, 160 and 02 MT per hectare in rice, maize and brinjal respectively under this region. So, all over views it was indicated that the adoptive farmers who adopted agro advisory services got benefit of Rs. 1190 to 5760 for cereals crop and from Rs. 1.2 lakh to 3.2 lakh and Rs. 4.0 to 8.40 lakh in vegetables and fruits crop respectively. This profit was due to the crop management done by the farmers according to agromet advisory bulletins. Thus, the application of agromet advisory bulletin, based on current and forecast weather is a useful tool for enhancing the production and income.